A MATHEMATICAL MODEL FOR THE DYNAMICS AND COST EFFECTIVENESS OF THE CURRENT CONTROLS OF CASSAVA BROWN STREAK DISEASE IN UGANDA. (2015) - KINENE, TONNY; LUBOOBI, LIVINGSTONE S.; NANNYONGA, BETTY; MWANGA, GASPER G.
No abstract available